POTENTIAL USE OF SOLAR RADIATION TO DESINFECT DOMESTIC WASTEWATER IN BRAZIL. - Sánchez-Román, Rodrigo M.; Soares, Antonio Alves; Sediyama, Gilberto C.; Matos, Antônio Teixeira de (Revista Brasileira de Engenharia de Biossistemas, 2008)
World's population growth is provoking an increasing demand of energy and clean water. Brazil is,mainly, a tropical country; therefore, it possesses a solar energy potential year round. Solar radiationis a promising energy source option, considering its non-pollutant nature, permanent readinessand cost zero. An alternative use for solar radiation is for disinfection of domestic wastewater(DWW), reducing environmental contamination and increasing water availability for agriculture.Solar radiation values for 202 meteorological stations dispersed in the Brazilian territory weredetermined. With these data and the model proposed by Sánchez-Román et al. (2007), it wascomputed the time of exposure necessary to disinfect DWW, to guarantee the World HealthOrganization's recommendation for agricultural purposes. 48 maps were developed consideringfour depths of DWW in the solar reactor. These maps showed the time of exposure required,anywhere in Brazil, to disinfect DWW reducing the coliform population from 3.5 x 106 NMP 100mL-1 down to 1.000 NMP 100 mL-1. It could be observed that the solar disinfection technology isapplicable in almost all the Brazilian territory during almost all year; and in some specific areas forat least eight months.